Prison types and inmates' psychosocial profiles: A comparison between medium and maximum security prison - Tajudeen Abiola; Aisha Y Armiyau; Laipo Adepoju; Owoidoho Udofia (Wolters Kluwer Medknow Publications, 2017)
Studies on the impacts the type of prison's environment had on the psychosocial well-being of their inmates were few. To contribute more study on this, the current study explored the psychosocial health profiles of inmates and the type of prison environment by comparing inmates' psychosocial profiles of a medium security prison to a maximum security correctional facility located in north central Nigeria. Participants were male inmates of medium security prison located in Bida, Niger-State and Jos maximum security facility in Plateau-State. All the participants filled the study instruments (i.e., a sociodemographic questionnaire, the ten-item personality inventory, resilience scale, and Oslo Social Support Scale) after obtaining informed consent from them. There was a significant positive association of prison types with resilience and social support which was reversed for spirituality. The multivariate analysis showed that inmates of medium security prison had significantly higher resilience and social support scores compared to those in maximum security correctional facilities. There was no difference in the five dimensions of personality among the inmates and in their experience of spirituality. The findings add to extant knowledge on the impact that the level of "indigenous" deprivations had on inmates psychosocial wellness factors. The study hence advocated to the department of correctional services to modify the indigenous measures that promote resilience and social support without compromising security.